Digital Content Marketing Strategy on the Milenialis.Id Instagram Social Media Account (@Milenialis.Id) for the Period January - February 2023 to Increase Brand Engagement - Mohammad Febry Tabrani; Erwan Sudiwijaya (Faculty of Leadership & Management, 2024)
E-Proceeding of 4th International Conference on Islam, Media and Communication (ICIMac 2024): “Communication & Digitisation in Madani Society”/ Muhammad Raqib Mohd Sofian, , Siti Suriani Othman, Safiyyah Sabri, Osama Kanaker & Ihab Ahmed Ra’uf Awais. 5th March 2024 Organized by : Faculty of Leadership & Management